Intuition : its powers and perils - Myers, David G. (Yale University Press, 2002)
Publisher's description: How reliable is our intuition? How much should we depend on gut-level instinct rather than rational analysis when we play the stock market, choose a mate, hire an employee, or assess our own abilities? In this engaging and accessible book, David G. Myers shows us that while intuition can provide us with useful--and often amazing--insights, it can also dangerously mislead us.